Protagonism of medical students in carrying out the activities of the HIPERDIA program: an experience report (Research, Society and Development, 2022)
Complications involving Systemic Arterial Hypertension and Diabetes Mellitus contribute to the increase in premature mortality from non-transmissible chronic diseases, as well as increase the costs of the Brazilian Unified Health System. The objective of this work was to dynamize the teaching-learning of Situational Strategic Planning to medical students, with the motto of the execution of the activities of the National Program of Hypertension and Diabetes.  The methodology used was the experience report of teaching-learning with the use of pedagogy by problems, leading the students to be the protagonists of their learning process under the coordination of the teacher. The execution of the programmed actions for the individuals in the community was developed in three moments, with home visits to actively search for the absent, invitation to participate in the programmed activities, and the performance of the actions inherent to the National Hypertension and Diabetes Program in the physical environment of the Family Health Strategy Unit. The results found were positive for the students' learning about Situational Strategic Planning, the formatting of the Intervention Plan, and the execution of health promotion actions. The concrete factors observed and pointed out here signaled a positive result in self-care, in the sensitization of the target audience and in the awakening of individuals to the knowledge about health promotion and prevention of the diseases in focus. For the medical students, the protagonism in the execution of the activities brought them closer to humanized care and provided a closer relationship between the Federal University of Pará and the community of Riacho Doce.